2015
DOI: 10.1007/s12010-015-1669-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Mannanase and β-Mannosidase Supplementation on the Total Hydrolysis of Softwood Polysaccharides by the Talaromyces cellulolyticus Cellulase System

Abstract: Softwoods are promising lignocellulosic feedstock that provide numerous fermentable sugars via the hydrolysis of the components of cellulose and mannan-type hemicellulose such as galactoglucomannan (GGM). However, fungal cellulase systems are insufficient for the hydrolysis of softwood GGM due to the relatively low levels of mannan-degrading activities. To compensate for the deficient activities in the cellulase system, mannan-degrading enzymes were added to a cellulase preparation from Talaromyces cellulolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
0
12
0
3
Order By: Relevance
“…Filamentous fungi are thought as the most efficient lignocelluloses degraders, especially T. reesei (Zhang et al, 2015; Wang et al, 2014), however, there is still an insufficient hydrolysis of lignocellulose due to the moderately low levels of mannan-degrading activity (Inoue et al, 2015). To compensate for the lower mannan-degrading activity, exogenous mannosidases have been added in the cellulase system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filamentous fungi are thought as the most efficient lignocelluloses degraders, especially T. reesei (Zhang et al, 2015; Wang et al, 2014), however, there is still an insufficient hydrolysis of lignocellulose due to the moderately low levels of mannan-degrading activity (Inoue et al, 2015). To compensate for the lower mannan-degrading activity, exogenous mannosidases have been added in the cellulase system.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the lower mannan-degrading activity, exogenous mannosidases have been added in the cellulase system. For example, in Talaromyces cellulolyticus the approximately 80% mannose yield was increased with high β-mannanase and β-mannosidase activities when supplemented with A. niger derived commercial enzyme (Inoue et al, 2015). It has been shown that the crystal of mannan can be degraded when endo-α-1,4-mannanase from T. reesei , endo-α-1,4-mannanase from A. niger and exo-α-1,4-mannosidase from A. niger are used (Hagglund et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting vector was cotransformed into T. reesei with plasmid TAkulox with pyr4 gene as a selective marker. Filamentous fungi are thought as the most e cient lignocelluloses degraders, especially T. reesei [40][41], however, there is still an insu cient hydrolysis of lignocellulose due to the moderately low levels of mannan-degrading activity [42]. To compensate for the lower mannan-degrading activity, exogenous mannosidases have been added in the cellulase system.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the lower mannan-degrading activity, exogenous mannosidases have been added in the cellulase system. For example, in Talaromyces cellulolyticus the approximately 80% mannose yield was increased with high β-mannanase and β-mannosidase activities when supplemented with A. niger derived commercial enzyme [42]. It has been shown that the crystal of mannan can be degraded when endo-α-1,4-mannanase from T. reesei, endo-α-1,4-mannanase from A. niger and exo-α-1,4-mannosidase from A. niger are used [43].…”
Section: Discussionmentioning
confidence: 99%
“…Optimash BG (Genencor International, Palo Alto, CA, USA) and Cellulosin GM5 from Aspergillus niger (HBI Enzymes Inc., Hyogo, Japan) were used to supplement acremonium cellulase and to enhance xylan and mannan digestibility in eucalyptus and DF, respectively (Inoue et al 2008(Inoue et al , 2015.…”
Section: Cellulosic Enzymesmentioning
confidence: 99%